The Impact of the Inclusive Library Program on Access to Higher Education for People with Disabilities - Wahyu Purnomo, Gabriel; Rizki Wikandani, Prayoga; Yuni Pratiwi, Kurniasih (Indonesian Journal of Disability Studies, 2025)
This study examines the impact of the inclusive library program on access to higher education for people with disabilities in Indonesia. The study used a quantitative method with a survey approach, involving 150 students with disabilities from ten universities. The main objective was to assess how inclusive library facilities, assistive technology, staff training, and institutional policy support contribute to increased access to education. The research findings show that while the availability of accessible facilities and assistive technology in libraries is crucial, it alone is not enough to improve access to higher education for people with disabilities significantly. Instead, comprehensive training for library staff and strong institutional policies significantly impact access to higher education, indicating that these elements are essential in creating a supportive and inclusive educational environment. These results underscore the need for a holistic approach to developing library services that meet the unique needs of students with disabilities. The study concludes that policymakers and educational institutions should prioritize these factors to foster an inclusive academic atmosphere.